The zookeeper's wife - Ackerman, Diane 1948- (New York W.W. Norton, 2007)
The true story of how the keepers of the Warsaw Zoo saved hundreds of people from Nazi hands. When Germany invaded Poland, Stuka bombers devastated Warsaw--and the city's zoo along with it. With most of their animals dead, zookeepers Jan and Antonina Zabinski began smuggling Jews into empty cages. Another dozen "guests" hid inside the Zabinskis' villa, emerging after dark for dinner, socializing, and, during rare moments of calm, piano concerts. Jan, active in the Polish resistance, kept ammunition buried in the elephant enclosure and stashed explosives in the animal hospital. Meanwhile, Antonina kept her unusual household afloat, caring for both its human and its animal inhabitants--otters, a badger, hyena pups, lynxes--and keeping alive an atmosphere of play and innocence even as Europe crumbled around her.--From publisher description. Read less
Includes bibliographical references (p. [343]-349) and index.
UCWS-3398g donated by Adrienne Maguddayao - December 2019
Keywords: Żabiński, Jan -- 1897-1974.; Żabińska, Antonina; Righteous Gentiles in the Holocaust -- Poland -- Warsaw -- Case studies; Zoo keepers -- Poland -- Warsaw -- Case studies; Warsaw (Poland) |x Ethnic relations